2012
DOI: 10.1111/j.1747-0285.2012.01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Receptor Structural Ensembles for Virtual Screening Using Binding Site Shape Analysis and Clustering

Abstract: Accounting for protein flexibility is an essential yet challenging component of structure-based virtual screening. Whereas an ideal approach would account for full protein and ligand flexibility during the virtual screening process, this is currently intractable using available computational resources. An alternative is ensemble docking, where calculations are performed on a set of individual rigid receptor conformations and the results combined. The primary challenge associated with this approach is the choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 69 publications
2
87
0
Order By: Relevance
“…Bioinformatics tools have become very important to pinpoint the targets for different ligands (Osguthorpe et al, 2012). Using bioinformatics tools we tried to evaluate whether citrus flavonoids are good ligands to some of the target proteins or gene related to diabetes such as glucokinase, glycogen synthase kinases 3Ī², peroxisome proliferator-activated receptor gamma, and dipeptidyl peptidase IV.…”
mentioning
confidence: 99%
“…Bioinformatics tools have become very important to pinpoint the targets for different ligands (Osguthorpe et al, 2012). Using bioinformatics tools we tried to evaluate whether citrus flavonoids are good ligands to some of the target proteins or gene related to diabetes such as glucokinase, glycogen synthase kinases 3Ī², peroxisome proliferator-activated receptor gamma, and dipeptidyl peptidase IV.…”
mentioning
confidence: 99%
“…Ī”G solv represents the electrostatic solvation energy of the complex, and Ī”G SA denotes the nonpolar contribution by the surface area (SA) to the solvation energy. The sorted compounds were clustered based on the Tanimoto coefficient between a set of linear fingerprint descriptors using Canvas (Schrƶdinger v9.6) (50,51).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, abundant crystal structures provided an alternative approach to sample protein flexibility of a certain target [31,32]. Some studies indicated that docking based on ensemble crystal structures outperformed that based on ensemble MD conformations [33]. The sufficient and diverse JAK2 crystal structures provided not only alternative docking proteins but also an implicit sampling of protein flexibility.…”
Section: Introductionmentioning
confidence: 98%